Does the digital economy reduce shipping-related pollution? Evidence from coastal port cities in China - Ding, Xingong; Song, Jiaqi; Zhu, Nian; Ji, Xina (Frontiers in Marine Science, 2025)
Air pollution caused by shipping-related activities has adversely affected public health and environmental quality in port cities. However, applying digital technologies offers new pathways to mitigate such pollution. Based on panel data from 52 coastal port cities in China from 2016 to 2020, this study employs a two-way fixed effects model to analyze the impact of the digital economy on shipping-related PM2.5 pollution. Additionally, a panel threshold model is used to examine the threshold effect of port size in the relationship between the digital economy and shipping-related pollution. Heterogeneity analysis is further conducted from two dimensions—vessel types and PM2.5 components—to explore the variations in the digital economy’s emission reduction effects. The results show that the development of the digital economy significantly reduces shipping-related PM2.5 pollution levels, and this emission reduction effect strengthens as port size expands. Furthermore, there are significant differences in the emission reduction effects across different vessel types and PM2.5 components. These findings contribute to understanding the mechanisms through which the digital economy mitigates shipping-related pollution and provide a scientific basis and policy support for promoting the green development of port cities and the shipping industry.